ChemInform Abstract: Iron‐Catalyzed Divergent Tandem Radical Annulation of Aldehydes with Olefins Toward Indolines and Dihydropyrans. Issue 18 (April 2016) - Lv, Leiyang; Qi, Longying; Guo, Qiaoxia; Shen, Baojian; Li, Zhiping
Abstract: The reaction proceeds via a radical pathway as is demonstrated by addition of an intermediately formed methyl radical (from tBu‐O‐O‐tBu) in absence of any aldehyde yielding compound (XVI) and the formation of indoline derivative (XVIII) when toluene is used as the solvent.